Analisis Nilai Malu Sebagai Cerminan Iman: Telaah Hadis Arba'in No. 20 - Mohammad Rizqy Aminullah; Mohammad Safaruddin; Mohammad Riezky Arya Pratama; Iklil Mufid; Mas' Odi (Program Studi Pendidikan Agama Islam Program Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
Shyness or modesty (haya’) is a noble character trait emphasized in Islamic teachings and considered a fundamental aspect of faith. Despite its significance, the value of modesty is often underestimated in contemporary social life, especially amid the increasing exposure to immoral behavior and the erosion of ethical boundaries. This study aims to explore the theological position of modesty in Islam and its practical implementation in daily social interactions. Employing a qualitative descriptive method, this research relies on literature studies and content analysis of Qur’anic verses, hadiths, and scholarly publications from recent years. The findings show that modesty is more than just personal timidity; it is a dynamic moral force that guides behavior, promotes self-restraint, and fosters a sense of responsibility toward others. Furthermore, modesty serves as a protective barrier that preserves individual dignity and social harmony. The study concludes that instilling the value of modesty is crucial in character education and remains relevant in addressing moral challenges in modern society. It is recommended that educational institutions and families incorporate this value systematically to strengthen ethical awareness from an early age.